Treasure is a creature not a creator - Baydoun, Ibtissam Ibrahim (Journal of Islamic Sciences, 2023)
Many people confuse truth with falsehood, leading them to engage in haphazard religious practices. They spread false hadiths and let their tongues loose using inappropriate language to refer to Allāh. Therefore, the problem addressed in this research is to expose the falsehood of a hadith that claims Allāh said, "I was a hidden treasure..." It also aims to highlight the prohibition of referring to Allāh as a "treasure" and the associated theological implications. Indeed, the knowledge of confirming the oneness of Allāh is the knowledge by which the attributes of Allāh are known, and it is the most noble of sciences because it is referring to knowing about the highest in status. Based on this, the importance of my research lies in the significance of the knowledge of confirming the oneness of Allāh, the most noble and essential of all sciences. Error in this field is a serious matter. I have confirmed that that Hadith is a lie about Allāh and His messenger ﷺ. Dozens of scholars of Hadith have mentioned that it is fabricated and it has no basis. Among them is Az-zarkashiyy, Al-^Asqalaniyy, and As-suyutiyy, also, the meaning of it is invalid. The research uses a historical retrieval methodology to examine the teachings of the Prophet ﷺ and an analytical and interpretive approach to clarify the meaning of key terms. Additionally, it utilizes an evidential methodology to prove the falsity of the hadith through logical and textual evidence. I express my recommendation by saying that we should monitor false hadiths that contradict Muslim beliefs, analyzing them and weighting them according to the scale of the Islamic Law, refuting them using corroborated academic data to clarify truths and defend the religion.